Law Enforcement Against Fiduciary Credit Guarantee Embezzlement by Debtors Based on Consumer Financing Agreements - Putro, Francisca Andriani; Rahaditya, R. (Dinasti Research, 2025)
This study examines the efficacy of legal enforcement in addressing the criminal offense of fiduciary collateral misappropriation by debtors under consumer financing agreements, with reference to Supreme Court Decision No. 419K/Pid.Sus/2021. Employing a normative- descriptive methodology, the research adopts statutory and case law analysis. The findings reveal inadequacies in current enforcement mechanisms, as the sentencing framework imposes disproportionately lenient penalties, thereby undermining their deterrent function. Further, the study identifies a normative conflict between the sanction provisions of Article 36 of Law No. 42 of 1999 on Fiduciary Security and Article 372 of the Indonesian Criminal Code (KUHP), which creates legal uncertainty and diminishes creditor protection. The analysis underscores the imperative of enhancing public legal awareness and fostering academic engagement in the dissemination of fiduciary law principles. To mitigate risks, the study proposes legislative reforms to harmonize penal sanctions and advocates for the institutional adoption of prudential measures by financing entities to deter fiduciary collateral fraud.